The effectiveness of multicomponent exercise combined with art therapy on balance, stress and anxiety among community dwelling elderly: a pilot study / Syafiqah Shuhaimi and Azliyana Azizan - Shuhaimi, Syafiqah; Azizan, Azliyana (Faculty of Medicine, 2024)
Introduction: According to the Department of Statistics Malaysia, the population aged 60 years and above has rose and Malaysia is estimated to be an aging country by 2030 as 15% of the population are elderly. As Malaysia's aging population increase, the physically inactive population increases. This study is to assess the effectiveness of eight weeks intervention of multicomponent exercise combined with art therapy on balance, stress, and anxiety among community-dwelling older adults. Methods: A single randomized trial control pilot study was conducted on 37 community-dwelling older adults were randomly allocated into three groups (i) multicomponent exercise (Exercise, n=12), (ii) multicomponent exercise combined with art therapy (Combined, n=13), (iii) art therapy (Art, n=12). Participants were given tasks according to groups allocated and needed to complete the task within eight weeks. Balance performance was measured via Time Up and Go test (TUG), while stress and anxiety were assessed via components in the Bahasa Malaysia version of the Depression Anxiety and Stress Scales (BM DASS-21). A repeated-measure ANOVA was used for data analysis. Results: Compared to the pre-intervention, all three groups showed a significant effect of time for balance performance, stress, and anxiety, (p<0.05) but no statistically significant differences in the three variables were found between the three groups (p>0.05). Conclusion: Eight weeks intervention of multicomponent exercise combined with art therapy had shown positive effect on balance, stress, and anxiety among community dwelling older adults. This study recommends integrating multicomponent interventions into rehabilitation program among older adults by healthcare practitioner particularly physiotherapist to achieve healthy aging.